EVALUASI SISTEM PENGENDALIAN STOCK BARANG JADI DI GUDANG PT.INDOCARE CITRA PASIFIK GROUP - Yeni Hernawati; Nanda Pramayasti Mulyadi; Trida Lestari; Daifulloh Faidz Rabbani (Jurnal Equilibrium Manajemen Fakultas Ekonomi Universitas Panca Bhakti, 2020)
The purpose of the study “Evaluation System Control Inventory of Finished Goods in Warehouse PT. Indocare Cintra Pasifik Group” is to find out how the system controls the warehouse againts the preparation of inventory of goods in PT. Indocare Citra Pasifik Group, which is a repository of inventory of medicines and skin care. Furthermore, how to handle it is carried out by the Warehouse Departement of PT. Indocare Citra Pasifik Group in managing and calculationg the physical inventory of finished raw materials. The research method that the researchers used in this study was the Descriptive Qualitative method of the researcher’s research result Direct interviews with employees of the Warehouse Department and Questionnaires distributed to Employees in the Warehouse Department at PT. Indocare Citra Pasifik Group. Research results obtained obtained a discrepancy in the inventory of goods in warehouse preparation and this is very dependent on the record of checking the suitability of the storage in the warehouse so that the implementation of the number of records is not in accordance with the existing inventory of goods .